STUDI KEANDALAN SISTEM DISTRIBUSI TENAGA LISTRIK AKIBAT PENGARUH DISTRIBUTED GENERATION (DG) - Christine Widyastuti (Sekolah Tinggi Teknik - PLN, 2016)
The research aims to analize the impact of installing DG to distribution system reliability. Evaluation of this distrubution syatem reliability use EDSA Technical 2005 software.There were seventh case studies in this research. The first is system without DG. The second to seventh case is by connect DG in bus change respectively by turns. The result of research show that by installing DG to each load bus always give improvement to distribution system reliability. The optimum reliability was obtained when DG was install at bus 4.